Students' Mathematical Literacy Ability In Solving Problems Viewed From Cognitive Style - Ahbi Mahdianing Rum; Dadang Juandi; Endang Cahya (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2026)
The differences in the characteristics of field dependent and field independent students in applying their mathematical literacy affect the results of students' work in solving mathematical problems. This study aims to identify students' mathematical literacy abilities viewed from cognitive style especially field dependent and field independent students in solving mathematical problems. This study uses a case study method with a qualitative approach which was carried out in one of the junior high schools in North Bengkulu Regency, Bengkulu Province, involving 32 students of class VIII in the 2022/2023 academic year who had studied number pattern material as participants. The subjects in this study were selected purposively, namely 3 students with a Field Dependent (FD) cognitive style. Data in the study were collected using the Group Embedded Figure Test (GEFT), mathematical literacy tests, and interviews. The research findings show that the majority of students have a cognitive style FI compared to FD. Most students achieved mathematical literacy skills at level 3. In terms of cognitive style, from the five levels of questions given, level 1-level 5, FD subjects with low, medium, and high initial mathematical abilities (KAM) achieved mathematical literacy up to level 3. The students met the formulate, employ and interpret indicators but still had difficulty writing mathematical symbols.